The Quality of Life Among Nursing Students Related to Stress and Academic Pressure in North Borneo Local University - Musa, Mazlinda; Majin, Rosnah; Mamat, Rohani; Noh, Malehah Mohd; Sa’at, Siti Fatimah (Indonesian Journal of Global Health Research, 2023)
Nursing students often face high levels of stress and academic pressure due to the demanding nature of their coursework, clinical rotations, and the responsibility of caring for patients. Therefore, the aim of this study is to identify the association between Quality of Life and stress plus academic pressure among nursing student in north Borneo local university. Material and Method – Cross sectional study design was used, with 55 respondents using Academic Pressure Scale (APS) and Overall Quality of Life scale (WHOQOLS) as the questionnaire was analyse using Chi-square test. Result – The probability value obtained from Pearson Chi-Square was 0.014 is less than predetermined alpha value (0.05), thus the null hypothesis was rejected. Conclusion: There is significant association between WHOQOL and the APS underscores the interconnectedness of students' perceived quality of life and their experience of academic stress.